Well‐based crystallization of lipidic cubic phase microcrystals for serial X‐ray crystallography experiments. Issue 10 (7th October 2019) - Andersson, Rebecka; Safari, Cecilia; Båth, Petra; Bosman, Robert; Shilova, Anastasya; Dahl, Peter; Ghosh, Swagatha; Dunge, Andreas; Kjeldsen-Jensen, Rasmus; Nan, Jie; Shoeman, Robert L.; Kloos, Marco; et al.
Abstract : A novel method is presented to screen for suitable crystallization conditions and produce large amounts of microcrystals of membrane proteins in lipidic cubic phase for serial crystallography experiments. Abstract : Serial crystallography is having an increasing impact on structural biology. This emerging technique opens up new possibilities for studying protein structures at room temperature and investigating structural dynamics using time‐resolved X‐ray diffraction. A limitation of the method is the intrinsic need for large quantities of well ordered micrometre‐sized crystals. Here, a method is presented to screen for conditions that produce microcrystals of membrane proteins in the lipidic cubic phase using a well‐based crystallization approach. A key advantage over earlier approaches is that the progress of crystal formation can be easily monitored without interrupting the crystallization process. In addition, the protocol can be scaled up to efficiently produce large quantities of crystals for serial crystallography experiments. Using the well‐based crystallization methodology, novel conditions for the growth of showers of microcrystals of three different membrane proteins have been developed. Diffraction data are also presented from the first user serial crystallography experiment performed at MAX IV Laboratory.